Chitosan nanoparticles for non-viral gene therapy - Fernandes, Julio C.; Tiera, Mareio José [UNESP]; Winnik, Françoise M. (My University, 2006)
The cationic polysaccharide chitosan has been widely used for non-viral transfection in vitro and in vivo and has many advantages over other polycations. Chitosan is biocompatible and biodegradable and protects DNA against DNase degradation. However following administration the ChitosanDNA polyplexes must overcome a series of barriers before DNA is delivered to the cell nucleus. This paper describes the most important parameters involved in the chitosan-DNA interaction and their effects of on the condensation, shape, size and protection of DNA. Strategies developed for chitosanDNA polyplexes to avoid non-specific interaction with blood components and to overcome intracellular obstacles as the crossing of die cell membrane, endosomal escape and nuclear import are presented. © 2006 American Chemical Society.